The Acti-Pair program helps men with prostate cancer increase physical activity with peer support: a mixed method pilot study - Baudot, Amandine; Barth, Nathalie; Colas, Claire; Garros, Maël; Garcin, Arnauld; Oriol, Mathieu; Collange, Fanny; Bongue, Bienvenu; Roche, Frederic; Chauvin, Franck; Bourmaud, Aurelie; Hupin, David (Frontiers in Public Health, 2024)
Background Although the health benefits of physical activity (PA) are recognised, prostate cancer patients do not follow PA recommendations. Barriers to PA, whether physical, environmental or organisational, are known. Furthermore, even when these barriers are overcome, this achievement is not systematically accompanied by lifestyle change. Many strategies have shown to be effective in increasing patient adherence to PA. This study aims to assess the feasibility and the viability of the Acti-Pair programme which combines three strategies: peer support, a personalised and realistic PA project, and support from health and adapted physical activity professionals in a local context. Methods and analysis We conducted a pilot study utilising a mixed qualitative and quantitative methodology, employing feasibility and viability assessments. Quantitative assessments included recruitment, retention adherence rates, process and potential effectiveness (PA and motivation) indicators; while qualitative methods were used to evaluate the programme's practicality, suitability and usefulness. Indicators of potential effectiveness were assessed before and after the intervention using a Wilcoxon test for matched data. Qualitative data were collected through semistructured interviews conducted by two researchers with various programme stakeholders. The study lasted for 3 years. Results Twenty-four patients were recruited over a 25-month period. Forty-two percent of patients completed the programme 3 months after the beginning. We recruited 14 peers and trained 9 peers over a 10-month period. The programme was coordinated extensively by adapted PA professionals, while health professionals were involved in recruiting patients and peers. Self-reporting of moderate to vigorous PA was increased after the Acti-Pair programme initiation (42.86 (30.76) at baseline to 53.29 (50.73)). Intrinsic motivation significantly increased after participation in the Acti-Pair programme (1.76 (1.32) before the intervention vs. 2.91 (1.13) after the intervention). The key player to support the Acti-Pair programme in the field has been the PA support system. The main challenge has been the difficulty of health professionals in promoting PA. Discussion This pilot study has shown that the Acti-Pair programme is feasible and viable. It will allow us to extend the peer support intervention to other contexts and assess the effectiveness of this intervention and its generalisation.